Transforming Bugis Language Learning Through Digital Approaches: A Study of the MGMP Workshop in Barru Regency - Rengko HR, Sumarlin; Muslimat, Andi Filsah; Pammuda; Kaharuddin, Mutahharah Nemin; Nasihin; Syam, Ridwan; Muri, Abdul Rauuf; Zaidul (Unram Journal of Community Service, 2025)
The rapid advancement of digital technology has brought new opportunities for preserving and revitalizing local languages in Indonesia. This study, titled “Transforming Bugis Language Learning through Digital Approaches: A Study of the MGMP Workshop in Barru Regency”, investigates the implementation of digital-based learning innovations for Bugis language teachers in Barru Regency. The workshop, attended by 30 members of the Musyawarah Guru Mata Pelajaran (MGMP) Bahasa Bugis, was designed to strengthen teachers’ competence in utilizing digital tools to enhance the teaching and learning of the Bugis language. Using a qualitative descriptive approach, the study explored participants’ experiences, learning outcomes, and perceptions toward the integration of technology in local language education. The findings indicate that the workshop significantly improved teachers’ understanding of digital pedagogy and their ability to design interactive learning materials using applications such as Quizizz, Baamboozle, and Canva. Participants reported higher confidence in developing engaging classroom activities that incorporate cultural elements of the Bugis language through multimedia and gamified platforms. Moreover, the workshop fostered collaborative learning and increased awareness of the importance of digital transformation in maintaining linguistic and cultural identity. This study concludes that digital approaches can play a vital role in transforming local language education by bridging traditional teaching with contemporary technological innovation. The MGMP workshop in Barru Regency demonstrates a practical model for empowering teachers and promoting sustainable language preservation in the digital era. The findings highlight the potential of integrating digital literacy and cultural education as complementary pathways to ensure that regional languages such as Bugis remain vibrant, relevant, and appreciated by younger generations.